Optical Character Recognition Untuk Manajemen Surat Masuk Dan Keluar - Indriyani, Indriyani; Hasibuan, Henni Novita Sari (Ali Institute of Research and Publication, 2022)
The system for managing incoming and outgoing mail at the Batang TORU Camat Office, Selatan Tapanuli includes incoming letters, outgoing letters, archives, and so on. Archives are a source of information from various fields that will be stored in storage areas. The purpose of writing this final project report is to find out how to handle incoming and outgoing mail manually and computerized at the Batang Toru Camat Office, Selatan Tapanuli filling by using the application and knowing the handlers of hadrcopy documents into softcopy online using optical character recognition (OCR). This Final Project report writing method is carried out by means of literature studies, observations and interviews with resource persons at the Batang Toru Camat Office, Selatan Tapanuli. From the results of observations and interviews, it is known that the handling of incoming and outgoing letters is carried out using a manual and computerized system. Incoming mail flow system starts from the recipient then is followed up to each unit and then archived. Outgoing mail is processed from drafting letters to sending outgoing letters. Electronic filing management (e-filing) using the application. Application of hardcopy documents that will be converted into softcopy using Optical Character Recognition (OCR) software, without having to type as the original. The software can be done online for free without registering first.